Who am I and What Keeps Me Going? Profiling the Distance Learning Student in Higher Education - Baxter, Jacqueline (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2012)
Student retention and progression has exercised the HE sector for some time now, and there has been much research into the reasons why students drop out of Higher Education courses. (Allen, 2006; Buglear, 2009;). More recently the Higher Education Academy Grants Programme Briefing (HEFCE, 2010) , outlined a number of areas that emergent project data revealed as being important to both the retention and progression of students, including areas outlined by a number of researchers as being essential to student success: expectations, support, feedback and involvement. But there has been less research, particularly within the distance learning sector, into factors that encourage students to stay (O'Brien, 2002). This small scale qualitative project using qualitative research methods and based in the Open University UK, builds upon an intensive institutional research project analyzing what type of interventions make a positive difference to student progression and success. The research revealed insights into factors linked to the expectations, identities and support of students which proved influential in terms of their resilience and motivation to remain on course.